Local Government's Role in Promoting Elderly Well-being : Strategies for Sustainable Aging Society Readiness - Srimethakul, Kumphol; Taomitr, Sornchai; Bodeerat, Chot (Journal of MCU Phetchaburi Review, 2025)
This article aims to study and analyze the aging situation at the global, regional, and national levels. It also examines the role of local administrative organizations under relevant legislation in enhancing the quality of life for the elderly—focusing on health, education, occupation, environment, and state-supported welfare and benefits. The article highlights the importance of preparing individuals before entering old age and developing an effective support system that ensures older people can live with dignity, good well-being, and continued engagement in their communities. In the 21st century, the world is entering an aging society at an unprecedented pace. The United Nations has designated October 1st as the International Day of Older Persons to emphasize the importance of older adults in society. Many countries across the globe, including those in the ASEAN region, are experiencing a rapid increase in the elderly population, significantly impacting economic, social, and public health systems. In Thailand, April 13th has been recognized as the National Day for Older Persons, and the country has formulated a National Plan for the Elderly to systematically and sustainably prepare for an aging society.